2007
DOI: 10.1007/s00464-007-9196-x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral laparoscopic inguinal hernia repair in patients with occult contralateral inguinal defects

Abstract: This study revealed 22% occurrence of bilateral inguinal defects in the patients who are diagnosed with pure inguinal hernia before surgery, with higher incidence for those with left inguinal hernia. It appears that routine contralateral groin exploration and evaluation during TEP is valuable. Patients with occult bilateral hernias are benefit from bilateral TEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 12 publications
3
39
0
4
Order By: Relevance
“…The study also found that left-sided hernias were 10.5 times more likely to present with bilateral hernias than were right-sided hernias, whereas female sex, age less than 50 years, and right-sided hernia were less likely to have bilateral hernia [19]. A more recent study also showed 22% occurrence of bilateral defects in patients with unilateral inguinal hernia at TEP [20]. Another retrospective study has shown that, while the incidence of bilateral hernia in clinically unilateral hernias at TEP is 7.97%, only 1.12% of patients with unilateral hernia repair (who had undergone contralateral evaluation at surgery) subsequently developed a hernia on the other side over a 10-to 80-month follow-up period [21].…”
Section: Discussionmentioning
confidence: 87%
“…The study also found that left-sided hernias were 10.5 times more likely to present with bilateral hernias than were right-sided hernias, whereas female sex, age less than 50 years, and right-sided hernia were less likely to have bilateral hernia [19]. A more recent study also showed 22% occurrence of bilateral defects in patients with unilateral inguinal hernia at TEP [20]. Another retrospective study has shown that, while the incidence of bilateral hernia in clinically unilateral hernias at TEP is 7.97%, only 1.12% of patients with unilateral hernia repair (who had undergone contralateral evaluation at surgery) subsequently developed a hernia on the other side over a 10-to 80-month follow-up period [21].…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, with the TAPP approach, an expeditious and low-risk evaluation of the contralateral side can be carried out during diagnostic laparoscopy [24]. The high rate of discrepancy between preoperative clinical findings and the intraoperative existence of bilateral inguinal hernias found by Bochkarev et al [23] makes one question whether the preoperative diagnostics were done accurately. In summary, with TAPP an unnecessary exploration of the contralateral side can be avoided.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in the total extraperitoneal patch plastic (TEP) technique, the indication for a bilateral procedure has to be found preoperatively [22] or additional preparation of the contralateral side has to be done to diagnose a potentially existing but preoperatively undiagnosed hernia. With this approach, Bochkarev et al [23] found an astonishing 22% of the patients with unknown hernias on the contralateral side. On the other hand, with bilateral preparation in the TEP technique, the preparation of the contralateral side is actually unnecessary in up to 78% of the patients, it takes time, and increases the risks.…”
Section: Discussionmentioning
confidence: 97%
“…17 Despite some authors find confusion of the ideal definition of occult hernia and argue that it may be just patent process vaginalis (PPV) and not a true hernia which may be not in need for repair, however, in other studies mentioned that there is no clear difference in between occult hernia and (PPV) and the natural history is same in both entities with risk of future symptomatic hernia which advocates repair of occult hernias once it is encountered in same settings without concern about its size. 14,15,18 In this study, routinely repaired the (COH) if present and during preperitoneal space dissection we noticed that even in small occult hernias there were always a muscular hernia defect which is in fact in the side of concomitant repair of the (COH) repair if it is found intraoperative, with no reported intra or post-operative significant complications or extended hospital stay.…”
mentioning
confidence: 58%